Formulation of polymeric particles with controlled charges by alkaline tempering. (17th April 2023) - Benyaya, Mathis; Bolzinger, Marie-Alexandrine; Chevalier, Yves; Bordes, Claire
Abstract: The control of surface charge of polymeric microparticles is a major challenge because electrostatic interactions stabilize their aqueous suspensions. In this study, anionic PMMA particles were prepared with 5 wt% of methacrylic acid as a comonomer. This comonomer was expected to give a negative charge to the particles, but none was observed from zeta potential measurements. The evolution of the zeta potential in alkaline medium was investigated to better understand this observation. It was demonstrated that the acid groups were present almost only in the core of the particles and that their deprotonation was possible using an alkaline tempering. Two phenomena occurred simultaneously leading to the charge appearance at the particle surface: i) the diffusion of hydroxide ions into the particles, allowing the migration of the negative charges to the particle surface with an appearance rate per mol of particles of 2.0 10 −3 m 3 mol −1 s −1 (multiplied by the hydroxyl ion concentration), and ii) the hydrolysis of ester groups of methyl methacrylate units characterized by a pseudo first order kinetics with k  = 3.0 10 −9  m 3  mol −1  s −1 . By carefully choosing the parameters of the tempering process, hydrolysis is minimized and anionic particles can be prepared with stable and controlled charges coming from the anionic comonomer. Doing so, anionic PMMA-like particles exhibited a stable zeta potential of −11.5 mV. Graphical abstract: Image 1 Highlights: Anionic PMMA particles were obtained using an alkaline tempering procedure. Surface charges are due to hydrolysis and diffusion of methacrylic acid monomers. The tempering process was needed for the methacrylic acid to diffuse to the surface. A core-shell particle diffusion model predicted the charges appearance kinetic.